The Effectiveness Of Modern Pedagogical Technologies In Teaching Geography - S.T. Abdurakhmanov; D.K. Ikromaddinova (TLEP – International Journal of Multidiscipline, 2025)
The article examines the effectiveness of modern pedagogical technologies in teaching geography. Interactive methods, multimedia tools, electronic resources, and project-based approaches contribute to students’ faster and more effective acquisition of subject knowledge. These technologies also foster independent thinking, practical skills, and problem-solving abilities among learners. The research findings highlight the critical role of pedagogical innovations in making geography lessons engaging, interactive, and efficient. Additionally, the study addresses the challenges associated with implementing these technologies and explores potential strategies for overcoming them.